DISTRIBUTION AND ABUNDANCE OF ODONATES FUANA OF TANAWAL REGION DISTRICT MANSEHRA, PAKISTAN - S. A. Mehmood; A. Zia; S. Ahmad; M. Shah; W. Ali4 Rababa; Irfanullah (Journal of Animal and Plant Sciences, 2021)
Throughout the present study a total of 425 specimens were collected to assess the distribution and abundance of Odonata fauna. Odonata is order of Dragonflies and Damselflies, their nymphs and adults are predators. They are environmental indicators and play important role in biological control of insect pests. Result revealed 19 species belonging to 02 suborders viz., Anisoptera and Zygoptera under 06 families. Most abundant family recorded was Libellulidae (74%) followed by family Chlorocyphidae and Calopterigidae (11%) and (7%) respectively. Whereas family Aeshnidae were found least abundant (2%). Genus Orthetrum (Newman, 1833) dominated with percentage (51%) followed by genera Rhinocypha (Rambur, 1842), Neurobasis (Selys, 1853) and Pantala (Hagen, 1861) 11%, (7%) and (7%) respectively. While least abundant genus was sympetrum (Newman, 1833) having percentage (2%). Highest richness is observed at locality Galli badral (12.47%) followed by Shungli (12.00%) and Phulra (11.29%) respectively. However lowest richness was recorded at locality Lassan (4.47%). Regarding species abundance Orthetrum triangulare triangulare (Selys, 1878) was dominated (18.11%) followed by O. purinosum neglectum (Rambur, 1842), (16.47%), Neurobasis chinensis chinensis (Linnaeus, 1758), (7.05%) and Rhinocypha quadrimaculata (Selys, 1853), (5.88%), respectively. While lowest abundance was observed for Ictinogomphus rapax (Rambur, 1842)  (1.41%).The canonical correspondence analysis showed thatall Odonata species were associated with submerged vegetation. Anisoptera and Zygoptera species were associated with sunny and shady biotypes. Two species; O. triangulare triangulare and O. pruinosum neglectum showed positive association with temperature. A Zygoptera species Megalestes major was found in moist habitat. Relative humidity was found as an influencing factor for the population growth of Anisopteran and Zygopteran species. Cluster analysis showed that all species were clustered into two groups; genera Anax Ictingomphus Crocothemis, Neurothemis, OrthetrumPalpopleura, Pantala and Sympetrum were clustered into group I. Wheras Group II comes up with all Zygoptera species. The current information/data base will be helpful in preservation of ecosystem management approaches of Odonata.
Keywords: Odonata; abundance; distribution; Cluster analysis; Canonical correspondence analysis; Tanawal